The conceptions and challenges of graduates in biological sciences participants of PIBID on the stage of problematization in the teaching of sciences by research (Revista Contexto & Educação, 2023)
Thinking and constituting problems in a teaching work plan or in an Investigative Teaching Sequence (SEI) is considered an essential moment, as it guides the other stages and allows the transition from naive curiosity to epistemological curiosity. In this sense, this research was carried out with Biological Sciences undergraduates, linked to the Institutional Scholarship Program for Teaching Initiation - PIBID and aimed to investigate the participants' conceptions and difficulties to problematize the Science contents of the Basic Education curriculum. After reading all the material, we opted for Textual Discourse Analysis (DTA) to organize, analyze and discuss the data collected, called the corpus. Under a reflexive bias, the participants indicated qualitatively how an investigative problem can hinder or enable different perspectives for the development of the stages of Teaching Science by Research (ECI).
Keywords: PIBID. Problematization. Science Teaching by Research.